Tumor acidity-induced charge-reversal liposomal doxorubicin with enhanced cancer cell uptake and anticancer activity. (June 2021) - Yang, Jinpeng; Yin, Zihe; Chang, Yincheng; Wang, Hua; Xu, Jiang-Fei; Zhang, Xi
Abstract: Concerning that the polyethylene glycol surface layer of DOXIL hinders cancer cell uptake, thus leading to low anticancer activity, it is of great importance to promote the cancer cell uptake of liposomal doxorubicin. Herein, we developed the charge-reversal PEGylated liposomal doxorubicin CRDOXIL with enhanced cancer cell uptake and high anticancer activity. Based on the tumor acidity-induced charge-reversal property, the cancer cell uptake of CRDOXIL could be significantly enhanced and the efficient caveolae-mediated endocytosis was achieved. Moreover, CRDOXIL maintained its stable PEGylated structure in neutral normal physiological environment, thus decreasing the side effects of doxorubicin on normal cells. Therefore, CRDOXIL exhibits high anticancer activity to cancer cells and low cytotoxicity against normal cells. It is anticipated that the charge-reversal strategy could be applied in diverse drug delivery systems to meet the requirement in chemotherapy. Graphical abstract: Image, graphical abstract